Discretionary Trade Policy and Excessive Protection - Staiger, Robert W.; Tabellini, Guido (American Economic Review, 1987)
This paper proposes a positive theory of tariff formation, based on the idea that the optimal trade policy may be time inconsistent. A benevolent government with redistributive goals may have an incentive to provide protection, since the redistributive effects of trade policy are larger if the policy is unanticipated. The suboptimal but time-consistent policy involves an excessive amount of protection. Furthermore, in a time- consistent equilibrium tariffs may dominate production subsidies. Thus, the requirement of time consistency can lead to a reversal of traditional normative ordering of tariffs and subsidies as instruments of trade policy.